Computational Analysis of the influence of Two Circumferential Grooves on Performance of Journal Bearing with Palm Oil as Lubricant - Sherif, Jamaluddin Md; Junaidi, Abd Khair; Asral, Asral; Arief, Dodi Sofyan (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2014)
This study compares the performance of a bearing with surface waviness liner to a plain bearing. Both bearings are functioned with palm oil as lubricant so that the potential advantages of the journal bearings could be identified. CFD analysis is developed to predict the numerical data for full film lubrication condition. A bearing of 60 mm in diameter with its ratio of length to diameter is 0.5, a clearance 250µm, and 200µm of wave amplitude is simulated. Semi circular wavy surface produces better results in term of load capacity than the plain journal bearing for a small eccentricity. The load carrying capacity is influenced by the increasing in speed of the shaft and the eccentricity ratio.